(untitled) (Swiss Medical Weekly, 2011)
Mechanical devices are sought to support insufficient or paralysed striated muscles including the failing heart. Nickel-titanium alloys (nitinol) present the following two properties: (i) super-elasticity, and (ii) the potential to assume different crystal structures depending on temperature and/or stress. Starting from the martensite state nitinol is able to resume the austenite form (state of low potential energy and high entropy) even against an external resistance. This one-way shape change is deployed in self-expanding vascular stents. Heating induces the force generating transformation from martensite to the austenite state while cooling induces relaxation back to the martensite state. This two-way shape change oscillating between the two states may be used in cyclically contracting support devices of silicon-coated nitinol wires. Such a contractile device sutured to the right atrium has been tested in vitro in a bench model and in vivo in sheep. The contraction properties of natural muscles, specifically of the myocardium, and the tight correlation with ATP production by oxidative phosphorylation in the mitochondria is briefly outlined. Force development by the nitinol device cannot be smoothly regulated as in natural muscle. Its mechanical impact is forced onto the natural muscle regardless of the actual condition with regard to metabolism and Ca2+-homeostasis. The development of artificial muscle on the basis of nitinol wires is still in its infancy. The nitinol artificial muscle will have to prove its viability in the various clinical settings.